Global existence and stability of a nonlinear wave equation with variable-exponent nonlinearities. Issue 8 (10th June 2020) - Ghegal, Samah; Hamchi, Ilhem; Messaoudi, Salim A.
ABSTRACT: In this paper, we consider a nonlinear wave equation with damping and source terms of variable-exponent types. First, we use the stable-set method to prove a global result. Then, by applying an integral inequality due to Komornik, we obtain the stability result.